Rapid identification of Penicillium marneffei by PCR-based detection of specific sequences on the rRNA gene - Vanittanakom N. (2014)
An emerging pathogenic dimorphic fungus, Penicillium marneffei, is one of the major causes of morbidity in patients with human immunodeficiency virus infection in Southeast Asia. A PCR-hybridization assay has been developed to identify this pathogen. This study describes the use of single and nested PCR methods for the rapid identification of P. marneffei. Two sets of oligonucleotide primers were derived from the sequence of 18S rRNA genes of P. marneffei. The outer primers (RRF1 and RRH1) were fungus specific. The inner primers (Pm1 and Pm2) were specific for P. marneffei and were used in nested or single PCR. The specific fragment of approximately 400-bp was amplified from both mold and yeast forms of 13 P. marneffei human isolates, 12 bamboo rat isolates, and 1 soil isolate, but not from other fungi, bacteria, and human DNA. The amplified products were analyzed by agarose gel electrophoresis followed by ethidium bromide staining. The sensitivities of the single PCR and nested PCR were 1.0 pg/μl and 1.8 fg/μl respectively. The assay is useful for rapid identification of P. marneffei cultures. Very young culture of P. marneffei (2-day-old filamentous colony, 2 mm in diameter) could be performed by this assay. The species was identified within 7 h (single PCR) or 10 h (nested PCR), compared to 4 to 7 days for confirmation of dimorphism. The application of these PCR methods for early diagnosis of the disease needs to be studied further.